Diagnostic accuracy of chromohysteroscopy in women with unexplained infertility - Chopra, Kanika; Trivedi, S. S.; Patra, Sharda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Chronic endometritis has been related to infertility but it is usually asymptomatic and the diagnosis is rarely suspected clinically. In cases of absence of any macroscopic abnormalities during conventional hysteroscopy, endometrial dyeing using methylene blue help identify abnormal areas and coupled with the histopathological examination gives a better diagnosis of endometritis. Methods: This study was conducted on 100 infertile women in Department of Obstetrics and Gynecology at Lady Hardinge Medical College, New Delhi over a period of one year. All women under- went hysteroscopy followed by chromohysteroscopy using 1% methylene blue dye. Biopsy was taken from light and dark stained areas. The histopathology results of these samples were compared and analyzed in relation with hysteroscopic and chromohysteroscopic findings and diagnostic accuracy calculated. Results: Out of 100 women who underwent dianostic hysteroscopy 68 cases had normal findings and 32 had abnormal finding and on chromohysteroscopy light staining pattern was seen in 56 cases and 44 cases had dark staining. Histopathology of biopsy tissue from these dark stained areas showed endometritis in 50% (22 out of 44 cases) and normal endometrium in 50% (22 out of 44) cases, and biopsy from light stained area showed chronic endometritis in 5.35% (3 out of 56) cases and remaining 94.65% had normal endometrium. Diagnostic accuracy of chromohysteroscopy were sensitivity=88%, specificity=70.66%, PPV=50%, NPV=94.6%. Conclusions: Chromohysteroscopy is a simple and effective technique for diagnosing endometrial pathology in cases of infertility.